Factors Associated With Fear of Falling and Functional Independence in Older Adult Living in an Iranian Nursing Home: A Cross-Sectional Study - Farideh Bastani; Masoumeh Birjandi; Hamid Haghani; Mohammad Reza Sobhan (Iran University of Medical Sciences, 2016)
Background: Fear of falling is common amongst older adults, especially those who live in nursing homes. This study aimed to determinate factors associated with fear of falling and functional independence in older adults living in nursing homes. Methods: This was a cross-sectional study using a convenience sampling method to enroll 200 older adults living in nursing homes from 25 senior centers in Tehran 1 and 2 districts between September 2015 and November 2015. Main outcome measurement instruments were the 16-Item falls efficacy scale international (FES-I, Persian version) and 11-Item Barthel index (BI) functional independence measure. In this study, variables were analyzed using Student's t test and ANOVA. The Pearson coefficient correlation was used to examine the relationship between FES and BBS[g1] . A 2-tailed P value < 0.05 was considered statistically significant. Results: The participants were mostly female (51.5%) and aged over 70 (mean age 76.89±8.50 years). Of 200 seniors within the study, 60.8% experienced one or more falls during the last year. Statistically significant relationships were found between the fear of falling and functional independence (r = - 0.524; P ≤ 0.001). There was a significant relationship between fear of falling and age (P = 0.039), history of falling (P=0.002), and chronic disease (P=0.009). In addition, there was a significant relationship between functional independence and some older adults' characteristics, including gender (P = 0.048), education level (P = 0.028), duration of living in nursing home (P=0.002), history of falling (P=0.006), and chronic disease (P=0.01). Conclusion: According to the findings, there was a high level of fear of falling in the older adults. The fear of falling in the older adults living in nursing homes is associated with age, history of falling, and chronic disease. There was a significant association between functional independence and variables of gender, education level, duration of living in nursing home, history of falling, and chronic disease.  [g1]Expand this term.